THE RELATIONSHIP BETWEEN PEERS INTERACTION, TIME MANAGEMENT, AND INTEREST LEARNING WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII - Yuliani Damayanti; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The low of students' mathematics learning outcome is associated with many factors. Not all peers support students' achievement. The lack of time management and the lack of studying interest are several factors that were assumed to have a relation with mathematics learning. Therefore, this study aimed to determine whether there is a positive and significant relationship between peers interaction, time management, and interest learning with mathematics learning outcomes in students class VIII of State Junior High School (SMP Negeri) 2 Banjarnegara in even semester in the academic year of 2016/2017. This research population was the students of VIII grade in SMP Negeri 2 Banjarnegara in 2016/2017, consisting of class VIIIB, VIIIE, VIIIF, VIIIG, VIIIH, totaling 165 students. Samples were taken from VIIIF as the research sample class and with the random sampling technique. The writer uses the questionnaire method to collect peer interaction, time management, and interest learning and test methods to get the resulting math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between peer interaction, time management, and interest learning with mathematics learning outcomes in students class VIII in even Semester of SMP Negeri 2 Banjarnegara in the academic year of 2016/2017. It is showed by Fcount  Ftable is 2,9232 ≥ 2,92227 with R= 0,4756 and R2 = 0,2262 with , with RC = , RC =  and RC =32,2185 , EC = , EC =  and EC = .